The Use of Video Subtitles in Increasing Students' Arabic Listening Skills - Raden Ahmad Barnabas; Fatwa Arifah; Ahmad Murodi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to determine the impact of subtitled videos on students' Arabic listening skills. This research uses a quantitative approach and a one-group experimental method. The pre-test is given before the treatment, and the post-test is given after the treatment. The data collection process uses observation, documentation and tests. The research sample was 60 first-semester students in an Arabic listening class. This research was carried out from September to December 2023. The results showed PAlpha (0.05) = 3.0329 (0.05), or t-count t-table = -21.1671 2.0009 . This means that subtitled videos positively impact learning to listen to Arabic. Students' listening skills have also improved compared to before using video subtitles. Individually, students' scores also increased 100%, and the lowest score was in class B. The results of this research have implications for stakeholders' understanding of implementing education to provide learning resources and multimedia technology in Arabic language classes. The findings recommend that teachers consider designing videos as Arabic language learning resources that can illustrate the special needs of listening courses or other courses